The influence of education level, income per capita, and consumption on the economic growth in East Java - Muhlisin,; Waspodo Tjipto Subroto,; Norida Canda Sakti, (Technium Social Sciences Journal, 2021)
This study explored the influence of education level, income per capita, and consumption on the economic growth in East Java with the population included all data in East Java. The data collection technique used a saturated sampling technique which explored the whole population in East Java. The source of data was from the publication data of East Java Central Bureau Statistics which was conducted using the documenter method. The data analysis used pane data regression which has been tested and proved to use the fixed-effect model as the preference. The result of the study showed that partially the level of education does not influence economic growth in East Java significantly, income per capita influences the economic growth significantly, and consumption also influences economic growth in East Java significantly. Therefore, stimulant testing in education level, income per capita, and consumption influence economic growth in East Java significantly.